Elementary school on the move– moving in elementary school - Reiner Hildebrandt-Stramann (Journal of Physical Education (Maringá), 2008)
Elementary school in Germany has changed during the last five years because, among other reasons, movement has entered it. The title's pun calls attention for two lines of work that characterize school pedagogy contemporary discussion. One of these lines is related to the last 15 years changing process at elementary school: it states that elementary school must be a learning and living place for children. The other line is related to movement pedagogy processes, which has been achieving higher and higher dimensions. Elementary school must be seen from movement point of view and must be transformed in a place for movement.